Screening for Sexually Transmitted Infection Pathogens in Semen Samples - RW Peeling; J Embree (Canadian Journal of Infectious Diseases and Medical Microbiology)
The transmission of sexually transmitted infection (STI) pathogens from an infected donor to the recipient of a semen donation in assisted conception may result not only in acute infection but also in long-term reproductive complications or adverse outcomes of pregnancy, including infection of the offspring. Screening for bacterial STI pathogens, Chlamydia trachomatis and Neisseria gonorrhoeae is strongly recommended because these pathogens can cause serious reproductive complications in the recipients of semen donations and infection in their offspring. Screening for these pathogens should be performed using the most sensitive methods, such as nucleic acid amplified tests. False-negative results due to inhibitory substances in the semen sample should be monitored using amplification controls. Where specimen transport is not a problem and culture facilities are available, N gonorrhoeae can also be detected by culture. Laboratories performing screening should subscribe to proficiency programs and have strict quality controls. Although Trichomonas vaginalis, group B streptococcus and genital mycoplasmas have been associated with adverse outcomes of pregnancy, the frequent finding of these organisms in healthy individuals brings into question the validity of mandatory inclusion of these organisms in the screening panel. Although viral STI pathogens and Treponema pallidum -- the causative agent of syphilis -- may be detected in semen, their presence may be more sensitively detected through antibody testing of the donor. Screening donors for HIV, hepatitis B and syphilis by serology is uniformly recommended in all of the guidelines, but the value of screening either donors or semen samples for cytomegalovirus, herpes simplex viruses and human papilloma viruses is less clear.